ИСТОРИЯ фортепианных кафедр ЕГК им.Комитаса - Арутюновна Апоян, Шушаник (Musical Armenia, 2010)
Historical Review: PhD candidate, professor in YSC after Komitas Shoushanik Harutyuni Apoyan writes her article about the history of Chair of Piano in YSC after Komitas. (See the beginning in the journal “Musical Armenia” 2007 N3-4 (26-27)).